IMPLEMEMTASI KURIKILUM MERDEKA DALAM PEMBELAJARAN DI SEKOLAH KRISTEN GIDEON KALABAHI - Markus Mauleti; Yessy Mata, Petrus Mau Tellu Dony, Halena Muna Bekata, Nehemia Fanpada, Trisnawasty Y. Daik, Imanuel (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to implement the Independent Curriculum in learning at Gideon Kalabahi Christian School. The method used is a qualitative research approach with a descriptive qualitative approach and is set at Gideon Kalabahi Christian Elementary School. The subjects in this study were teachers of grades IA, IB, IVA, and IVB, and students. Data collection methods used interviews, observation, and documentation. The data analysis used descriptive qualitative data analysis. The data collection techniques used were interviews, observation, and documentation. Meanwhile, the data analysis techniques used were data reduction, data presentation, and conclusions. The results of this study can be concluded that the implementation of the Independent Curriculum-based learning at Gideon Kalabahi Christian Elementary School has followed the stages in accordance with the Independent Curriculum concept. Although there were obstacles such as the lack of student or teacher handbooks, the results showed that teachers used learning resources relevant to the learning.